Chief Justice Rose Bird's State of the Judiciary Address at State Bar Annual Meeting - Watkins, Howard::::::::: (1985)
Chief Justice Rose Bird at lectern receiving standing ovation; Incoming State Bar President David Heilbron, Outgoing State Bar President Burke Critchfield